Definition of the death of seismic events by using digital channel data of the Main center of special control and foreign seismic stations - Andrushchenko, Yu. A.; Osadchy, V. I.; Lyashchuk, A. I.; Grabchenko, V. V. (Geofizicheskiy Zhurnal, 2018)
Among the main parameters of the source of the seismic event, the depth of the hypocentre is of greatest interest, which, as a rule, is determined with the least accuracy. The knowledge of the exact spatial position of the earthquake foci makes it possible to reveal their connection with the features of the structure of the earth’s crust, primarily with active faults. The solution of these problems is primarily ensured by the use of observational data obtained with the help of local, regional or global networks of digital seismic stations, as well as by improving computer technologies and methods of processing digital seismic data. To determine the parameters of low-energy seismic events, the epicenters of which are located within the platform part of the territory of Ukraine, it is expedient to use the data of instrumental observations obtained with the help of the regional network of digital seismic stations of the Main Center for Special Control (MCSK) of the State Space Agency of Ukraine. To increase the accuracy of localization of seismic events, it is necessary, on the one hand, to significantly expand the network of seismic observations, and on the other, to improve the methods for determining the basic parameters of earthquakes. The article analyzes the basic methods for determining the depths of the hypocenters of seismic events. The program-mathematical support allowing to make the depths of the earthquake foci by records of reflected waves and from the data of macroseismic observations is considered. To estimate the depth of seismic sources from the data of digital seismic channels of the MCSK and foreign seismic stations, the amplitude-frequency characteristics of which are available in the «Geotool», a specialized program «Assessment of depth» has been developed. A number of foreign and domestic seismic stations, most suitable for clarifying the depths of hypocenters of earthquakes from the area of the Vranch Mountains, has been determined. A method for determining the depth of an earthquake source from the area of the Vranch Mountains using data from digital seismic stations located at distances of 20—40 km from the center of a seismically active zone is proposed.